The Transformation of Public Elementary School Governance in a Pesantren Community: A Study of Hybrid Educational Governance at SDN Potoan Daja, Pamekasan, Madura - Afandi Afandi (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
The governance of public elementary schools (SDN) in regions dominated by pesantren culture faces institutional pressures that differ from those of public elementary schools in general; however, the patterns of adaptation have not been extensively studied empirically. This study analyzes the transformation of governance at SDN Potoan Daja, Pamekasan, Madura, through the lens of hybrid educational governance. A qualitative approach with a case study design was employed; data were collected through participatory observation, semi-structured in-depth interviews, and document analysis involving the school principal, teachers, the school committee, parents, community leaders, pesantren figures, and village officials during the period of April–October 2025. Analysis was conducted interactively using data reduction, thematic categorization, and continuous field verification. The research findings indicate that the governance of SDN Potoan Daja has evolved through a fusion of the state’s formal bureaucratic system and the pesantren’s socio-cultural mechanisms. The integration of religious activities into school culture, the involvement of pesantren leaders in decision-making, and the strengthening of participatory relationships between the school and the community have proven to build social legitimacy that cannot be achieved through formal regulations alone. The low level of community interest in public elementary schools is not due to a rejection of formal education, but rather concerns about the loss of religious values. When public elementary schools integrate pesantren culture into their governance, community trust increases. This study confirms that a hybrid educational governance perspective is more appropriate for understanding the dynamics of primary education governance in religious areas than a formal bureaucratic approach. These findings contribute to the development of a community-based education governance model and serve as a reference for SDN management policies in areas with a pesantren context.